Standardization of a High‐Quality Methodological Framework for Long‐Term Genetic Monitoring of the French Wolf Population - Agathe Pirog; Christophe Duchamp; Cécile Kaerle; Caroline Dufaure de Citres; Sabine Rousselot; Juliette Lavarec; Guillaume Queney (Ecology and Evolution)
ABSTRACT Since the gray wolf was eradicated from large parts of Europe, this species has been recolonizing much of its former distribution, particularly since the past 30 years. Wolves benefit from European legal protection through the Habitats Directive and the Bern Convention, and reporting on the evolution of their populations in each country of Europe is mandatory. To monitor French wolf populations over the long term, a standardized high‐quality methodological framework has been developed to analyze data from noninvasively collected samples and assess population diversity. We delineated each step and implemented a laboratory control procedure to analyze 8733 samples harvested within the French distribution range of the species between 2006 and 2022, and provided key quality and diversity indicators. Of these samples, 82.8% were successfully amplified and sequenced for the mitochondrial control region. Subsequently, the wolf samples were genotyped at 22 microsatellite autosomal loci and a sex locus displayed over two independent multiplexes using the multitube approach. The average success rate of polymerase chain reaction per locus was 64.2% across all replicates. The residual genotyping error rates were low compared to those in other studies using non‐invasively collected samples, with mean residual allelic dropout rates of 5.8% per locus and mean residual false allele rates of 1.0% per locus. The high‐quality dataset identified 1735 individuals in total over the last 15 years, of which 99.9% exhibited a single Italo–Alpine mitotype. Genetic diversity was relatively low, with mean observed heterozygosity of 0.482 and mean expected heterozygosity of 0.519. This supports the natural colonization of the French Alps by a few individuals originating from the remaining Italian populations, which started approximately 30 years ago. By generating high‐quality standards and quality control processes, this protocol enhances the cost‐efficiency ratio of monitoring French wolf populations and holds high value for managers tasked with the management and conservation of wolf populations in the long term.